Ocean Energy Unleashed: A Sustainable Frontier in the Indian Ocean - Basu, Rahul (Journal of Science and Technology, 2026)
The vast expanse of the Indian Ocean holds untapped energy riches, waiting to be harnessed. Its impact is palpable during natural calamities-tsunamis, tidal surges, and inland floods. Climate change, with pollution from fossil fuels, has intensified the search for alternative energy fuels. Ocean power development has traditionally centered on regions with robust tidal forces, yet littoral nations bordering the Indian Ocean are making strides in Blue and Green Technology. Like hydroelectric dams, power plants at river estuaries harness tidal water, releasing it to generate electricity. India’s tidal energy potential is estimated at 9,000 MW. Devices floating on the ocean surface or anchored to the seabed convert wave motion into power. Underwater turbines, akin to wind turbines, tap marine currents for electricity. Lower-velocity currents hold promise for large-scale projects. The temperature contrast between warm surface waters and cold depths can drive steam-based power generation through Ocean Thermal Energy Conversion (OTEC). India’s coastline harbors around 54 GW of ocean energy potential-12.45 GW from tides and a whopping 41.3 GW from waves. Currents in the Macpherson Strait near Andaman Island offer hydrokinetic energy. Prototype turbines have been tested, hinting at an annual energy potential of 4.8 MWh/m. Despite a 7,600 km-long coastline, India lacks operational offshore wind plants. Gujarat and Tamil Nadu alone account for 71 GW of offshore wind energy potential by 2050. Other regions and hybrid projects hold promise and are also discussed. This paper provides a comprehensive review of the untapped potential of ocean energy in the Indian Ocean, emphasizing India’s capacity, ongoing developments, and future project proposals. The paper aims to contribute by analyzing specific technologies and estimating their feasibility in real-world applications, filling gaps in current research by focusing on geographic, economic, and technical challenges.